Correlation Between Emotion Regulation And Self-Harm Tendencies in College Students - Adinda Widya Ramadhana Putri; Dyta Setiawati Hariyono (Universitas Katolik Soegijapranata, 2023)
The individual's inability to solve problems causes distress, leading to negative emotions or affect. Some of the negative feelings that college students experience are, for example, working excessively, smoking, drinking alcoholic beverages, consuming drugs, or self-harming. College students should be able to make problem-solving plans correctly based on problem-solving steps and evaluate themselves to relevant arguments in solving problems. At least college students do not do self-harm behavior as a coping in their lives because students are judged to be able to think well in dealing with the problems they face. The purpose of this study was to determine the relationship between emotion regulation and self-harm tendencies in college students. This research method uses a quantitative approach to the type of correlational research. Sampling in this study used an incidental sampling technique. The subjects of this study were college students who were active in learning at the University of Muhammadiyah Banjarmasin, with as many as 312 subjects. The scale used in this study is the emotion regulation scale and the self-harm tendencies scale, with the scaling model being the Rating scale. The results of this study show that there is a negative and significant relationship between emotion regulation and self-harm tendencies in college students, with a coefficient (r) of -232 and a value (Sign.) of 0.000. This means if the emotional regulation is higher, the self-harm tendencies are lower. Meanwhile, emotional regulation is insufficient, and self-harm tendencies are higher.